2019
DOI: 10.1186/s12939-019-0999-x
|View full text |Cite
|
Sign up to set email alerts
|

Age and regional disparity in HIV education among migrants in China: migrants population dynamic monitoring survey, 2014–2015

Abstract: Objective A lack of education among migrants remains an important but overlooked issue that indirectly contributes to HIV transmission. It is necessary to know who has received HIV education and who has a lower probability of being educated among migrants across different regions and age groups in China. Methods We used pooled data from the 2014 and 2015 Migrants Population Dynamic Monitoring Survey. The study population included 406,937 Chinese migrants. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…The frequently changing government regulations on health services and prevention planning for migrant population have increased uncertainty in policy implementation and exposed migrant populations to the risk of HIV transmission [ 49 ]. A survey using national demographic data has showed that areas with a higher HIV prevalence have higher rates of HIV-related education among migration population; compared with the central and western regions in China, in the eastern coastal areas with more medical and financial resources, the proportion of migrant population who have received HIV education is relatively low [ 50 ]. Hence, health care resources need to be allocated to areas with large migrant populations so as to provide better health care for migrant workers.…”
Section: Discussionmentioning
confidence: 99%
“…The frequently changing government regulations on health services and prevention planning for migrant population have increased uncertainty in policy implementation and exposed migrant populations to the risk of HIV transmission [ 49 ]. A survey using national demographic data has showed that areas with a higher HIV prevalence have higher rates of HIV-related education among migration population; compared with the central and western regions in China, in the eastern coastal areas with more medical and financial resources, the proportion of migrant population who have received HIV education is relatively low [ 50 ]. Hence, health care resources need to be allocated to areas with large migrant populations so as to provide better health care for migrant workers.…”
Section: Discussionmentioning
confidence: 99%
“…The frequently changing government regulations on health services and prevention planning for migrant population have increased uncertainty in policy implementation and exposed migrant populations to the risk of HIV transmission [40]. A survey using national demographic data showed that areas with a higher HIV prevalence have higher rates of HIV-related education among migration population; compared with the central and western regions in China, in the eastern coastal areas with more medical and nancial resources, the proportion of migrant population who received HIV education was relatively low [41]. Hence, health care resources need to be allocated to areas with large migrant populations so as to provide better health care for migrant workers.…”
Section: Discussionmentioning
confidence: 99%
“…Developing countries, represented by China, have problems in AIDS prevention education, such as outdated education model, poor effect of education, and uneven distribution of educational resources [ 5 , 6 ]. Therefore, it is necessary to develop innovative AIDS education.…”
Section: Introductionmentioning
confidence: 99%